Maternal Characteristics Affect Fetal Growth Response to Maternal Supplements in the Women First Preconception Trial (WF) (P10-017-19). (13th June 2019) - Hambidge, Michael; Bann, Carla; McClure, Elizabeth; Westcott, Jamie; Garces, Ana; Dhaded, Sangappa; Ali, Sumera; Krebs, Nancy; Group, Women First Study
Abstract: Objectives: Determine if maternal characteristics modified newborn anthropometric outcomes in the WF trial ( ClinicalTrials.gov NCT01883193 ). Methods: Secondary analysis included combined data for all 1465 maternal infant dyads in WF sites in Guatemala, India, and Pakistan who had 1 st trimester ultrasounds and newborn anthropometry with the three WF arms maintained: Arm 1 commenced a comprehensive nutrition supplement ≥3 months prior to conception; Arm 2 commenced the same supplement in the 1 st trimester, and Arm 3 received no trial supplements. Maternal characteristics included were: baseline, BMI, hemoglobin, age, education, SES, and parity plus newborn sex. Newborn outcomes were Z-scores for length (LAZ), weight (WAZ), and weight-to-length ratio (WLRZ). Mixed effect regression models were fit for each outcome, including treatment arm, effect modifier, and treatment arm x effect modifier interaction as predictors and controlling for study site, maternal characteristics, and newborn sex. Results: Parity, anemia and newborn sex were significant effect modifiers favoring para 0 vs para ≥1, anemia vs non anemia, and newborn male vs female. Effect of Arm 1 vs 3 was significantly larger for para 0 vs ≥1 women on length and weight (Table). Arm 2 vs 3 was not associated with improvements for para 0 in weight ( P  = 0.273) or WLRZ ( P  = 0.710). Arms 1 and 2 (vs 3) were associated with significantly higher length, weight, and WLRZ for anemic women. For parity and anemia, effect sizes for Arm 1 were greater than for Arm 2 for WAZ and WLZ ( P  < 0.05), but not LAZ. Arm 1 and 2 were associated with significantly higher weight and WLRZ for male vs female newborn. Conclusions: In diverse low resource populations, impaired fetal growth (weight and length) is substantially improved in nulliparous and in anemic women but minimally or not at all in parous and in non-anemic women. Correction of weight decrements is most pronounced with improvement in maternal nutrition commencing prior to conception. Funding Sources: Bill & Melinda Gates Foundation; NIH, NICHD and ODS. Supporting Tables, Images and/or Graphs: